Antimicrobial resistance and genetic relationships of enterococci from siblings and non-siblings Heliconius erato phyllis caterpillars - Huff, Rosana; Inhoque Pereira, Rebeca; Pissetti, Caroline; Mellender de Araújo, Aldo; Alves d’Azevedo, Pedro; Frazzon, Jeverson; GuedesFrazzon, Ana Paula (PeerJ, 2020)
Background Studies evaluating bacteria in insects can provide information about host–microorganism–environment interactions. The gut microbial community has a profound effect on different physiological functions of insects. Enterococcus spp. are part of the gut community in humans and other animals, as well as in insects. The presence and antimicrobial resistance profile of enterococci are well studied in different animals; however, data for Heliconius erato phyllis (Lepidoptera: Nymphalidae) do not yet exist. Therefore, the aims of this study were to evaluate the distribution of enterococcal species, their antimicrobial resistance profile and virulence genes, and the genetic relationships between enterococci isolated from fecal samples from sibling and non-sibling H. erato phyllis caterpillars collected from different sites in South Brazil. Methods Three H. erato phyllis females were captured (two from a forest fragment and one from an urban area), and kept individually in open-air insectaries. Eggs were collected and caterpillars (siblings and non-siblings) were fed daily with Passiflora suberosa leaves. Fecal samples (n = 12) were collected from fifth-instar caterpillars, inoculated in selective medium, and 15 bacterial colonies were randomly selected from each sample. Enterococci were identified by PCR and MALDI-TOF, analyzed by disk diffusion antimicrobial susceptibility tests, and screened for resistance and virulence genes by PCR. The genetic relationships between the strains were determined using pulsed-field gel electrophoresis (PFGE). Results A total of 178 enterococci strains were identified: E. casseliflavus (74.15%; n = 132), E. mundtii (21.34%; n = 38), E. faecalis (1.12%; n = 2) and Enterococcus sp. (3.37%; n = 6). High rates of resistance to rifampicin (56%) and erythromycin (31%) were observed; 120 (67.41%) of the isolates showed resistance to at least one antibiotic and six (3.37%) were multidrug-resistant.None of the erythromycin-resistant strains was positive for the erm(B) and msrC genes. The virulence genes esp, ace, and gelE were observed in 35%, 7%, and 1% of the strains, respectively. PFGE separated the enterococci into 22 patterns, four being composed of strains from sibling caterpillars. Conclusion Enterococcus casseliflavus was the dominant species in fecal samples of fifth-instar caterpillars. Resistant enterococci strains may be related to environmental pollution or the resistome. The PFGE analysis showed genetic relationships between some strains, suggesting that the enterococci isolated from fecal samples of the sibling caterpillars might have come from common sources, e.g., via diet (herbivory) and/or vertical transmission (through the egg surface). Further studies will be conducted to better understand the role of Enterococcus in the microbial community of the gastrointestinal tract of these insects, and the mechanisms involved in acquisition and maintenance of enterococci.
Keywords: Lepidoptera; Enterococcus casseliflavus; Molecular typing; Antimicrobial profile; Enterococcal species